Fetal and maternal responses to high feed intake from day 29 to 45 of gestation - R E Musser; J W Smith II; L L Burum; C J Samland; Duane L Davis; Robert D Goodband; Michael D Tokach; Jim L Nelssen; Theresa J Rathbun; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1997)
Parity-four sows were fed either 4.0 Ib/d (control, n = 6) or 14.0 Ib/d (high, n = 9) of feed from d 29 to 45 of gestation. On d 45 of ges~tion, sows were slaughtered and uteri collected for fetal and placental measurements. High-feed-intake sows gained more weight from. d 29 to 45 compared to control sows. Providing feed in excess of established requirements to gestating sows from d 29 to 45 of gestation increased IGF-I concentrations in maternal plasma and decreased crown-rump length variation of the fetus. Increased feed intake resulted in a removal of the correlation between average fetal weight and number of fetuses per sow. We postulate that the increased maternal IGF-I or other maternal responses to high feed intake altered the maternal limit on fetal growth at this stage of gestation.; Swine Day, Manhattan, KS, November 20, 1997
Keywords: Swine day; 1997; Kansas Agricultural Experiment Station contribution; no. 98-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 795; Swine; Feed intake; Fetal growth; Insulin-like growth factor